2022
DOI: 10.14740/cr1441
|View full text |Cite
|
Sign up to set email alerts
|

A Significant Effect of Oral Semaglutide on Cardiovascular Risk Factors in Patients With Type 2 Diabetes

Abstract: Background:The once-daily glucagon-like peptide 1 (GLP-1) analogue, liraglutide has been shown to reduce major adverse cardiovascular events (MACE) and progression of chronic kidney disease (CKD). The once-weekly GLP-1 analogue, semaglutide also reduced MACE and renal events. Based on the evidence for GLP-1 analogues on MACE and renal events, the guideline recommended to treat highrisk diabetic individuals with GLP-1 analogues to reduce MACE and CKD progression. Recently, a once-daily oral semaglutide was deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…In the PIONEER 6 trial, low-density lipoprotein (LDL)-cholesterol and triglyceride levels were modestly lower in the oral semaglutide group, 21 while in other studies, a significant decrease in LDL-cholesterol and non-high-density lipoprotein-cholesterol was observed during oral semaglutide treatment. 20 In the study by Dahl et al., 22 a significant decrease in very low-density lipoproteins, apolipoprotein B48, and triglycerides was observed after 12 weeks of treatment with oral semaglutide at a dose of 14 mg daily.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the PIONEER 6 trial, low-density lipoprotein (LDL)-cholesterol and triglyceride levels were modestly lower in the oral semaglutide group, 21 while in other studies, a significant decrease in LDL-cholesterol and non-high-density lipoprotein-cholesterol was observed during oral semaglutide treatment. 20 In the study by Dahl et al., 22 a significant decrease in very low-density lipoproteins, apolipoprotein B48, and triglycerides was observed after 12 weeks of treatment with oral semaglutide at a dose of 14 mg daily.…”
Section: Discussionmentioning
confidence: 94%
“…No significant effect on blood pressure values was observed during oral semaglutide treatment in the present study, although initial values were in the range of hypertension; this contrasts with the results of some other studies, where significant decreases in systolic blood pressure values were observed. 20,21 In the analysis of all PIONEER studies, blood pressure remained similar, or was slightly reduced over time, in patients treated with oral semaglutide compared with active comparators. 7 In addition, the present study did not reveal significant effects of oral semaglutide on lipid parameters.…”
Section: Discussionmentioning
confidence: 98%
“…While there is still no significant evidence that oral semaglutide can reduce the rates of cardiovascular events in people with T2D, this finding may rely on a supposed “class effect” of GLP-1RA in protecting from cardiovascular disease [ 20 ]. In addition, oral semaglutide can improve cardiovascular risk factors [ 6 ], and a pooled analysis of the SUSTAIN-6 and PIONEER-6 trials identified a strong consistency in the effects on cardiovascular outcomes of injectable and oral semaglutide [ 21 ]. The effects of oral semaglutide on cardiovascular outcomes in individuals with T2D and established atherosclerotic cardiovascular disease and/or chronic kidney disease are being tested in the SOUL trial [ 9 ], the results of which are expected to be presented in 2025.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of patients with T2D with oral semaglutide results in an improvement of cardiovascular risk factors [ 6 ]. Although there is still no evidence that oral semaglutide improves cardiovascular outcomes of T2D, the same active compound, when administered subcutaneously in the SUSTAIN-6 trial, reduced the rate of 3-point major adverse cardiovascular events (3P-MACE) compared to placebo [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, one also needs to consider other possible indirect influences that orally administered butyrate may have on serum lipids, for example by stimulating the secretion of glucagon-like peptide 1 (GLP-1) [ 24 , 25 ]. The latter is an established enhancer of β cell function and insulin secretion [ 24 , 25 ], but there is also emerging evidence that GLP-1 agonists can lower serum LDL-C [ 26 , 27 ]. Therefore, while our in vitro studies give insights into the possible effect of butyrate on hepatic lipid metabolism in an in vitro setting, the question of whether butyrate can have beneficial effects on plasma lipids ultimately requires in vivo studies.…”
Section: Discussionmentioning
confidence: 99%